Implantação do controle estatístico de processo: um estudo de caso em uma empresa do setor alimentício - Marcos, Elizangela de Lima [UNESP] (2014)
The purpose of this dissertation is to analize the implentation of the SPC (Statistical Process Control) for the management of operations in a food company. Furthermore, it was performer a theoretical review that includes: Quality Control, Process Variability and SPC. This theoretical review supported this case study, and it has possible to describe and discuss all the steps of deployment the tool in the new System of Management. In addition, to suggest a proposal of a guide to aid the implementation of the SPC in manufacturing processes. The results reveal that comprise a corporative guide may not be effective, when this is not analyzed in a techinical dimension of applicability on the local to be used. Moreover, the point observed in the results, all the System of Management need to formalize a standard applicatibility of management tools, avoiding common mistakes; for instance, non-existence of a study to identify which equipment or point of operatio must be monitored